Urban/village extension - design principles of new urbanism: the case studies of Poundbury and Upton - Lei, Yanhui (2014)
The motivation for this research is based on the very serious problem – local identity loss of village extensions in the Chinese ordinary villages. During the new development of Chinese ordinary villages, international concrete blocks and multi-storey apartments, which have been mass-produced in urban areas, are simply copied into rural areas replacing the local distinctive built environment. The author of this thesis set out to rethink the design principles of new urbanism in a way which can help create an urban/village extension of a town or a village to respect local identity or local context. Therefore, the research question is that ‘Can the design principles of new urbanism promote local identity or harmony with local context for urban/village extension? By reviewing the primary theories and ideas, the literature review draws upon primary sources of new urbanism including introduction and design principles which underlies a fundamental theoretical framework of design principles of new urbanism, and the overall view of the practice. Once the framework of design principles of new urbanism have been established in this research, it is essential to test it through case studies. The purpose of case studies is to identify if the design principles of new urbanism can promote local identity or harmony with local context in practice. Two UK cases, Poundbury and Upton were selected and analysed. During case studies, the interview plays an important role in modifying the design principles of new urbanism which direct the analysis of the physical environments of Poundbury and Upton. The initial outcomes are expected to confirm that the design principles of new urbanism could promote local identity or harmony with local context based on the case study findings. In order to further investigate these outcomes, factual information was collected through questionnaires administered face-to-face and on-the-spot to the residents of Poundbury and Upton. The findings of the questionnaire provided strong investigated evidence along with the initial outcomes addressed by literature review and the case studies. Finally, it can be concluded that the design principles of new urbanism are appropriate to promote local identity or harmony with local context for creating an urban/village extension. Keywords: urban/village extension, design principles of new urbanism, local identity, harmony with local context.